Long-term goflkicept therapy for patients with idiopathic recurrent pericarditis: results of the interim analysis of an ongoing open-label extension study - Valentina Yu. Myachikova; Alexey L. Maslyanskiy; Olga M. Moiseeva; Margarita L. Schedrova; Alina N. Egorova; Еkaterina G. Ponomar; Mikhail Yu. Samsonov (Терапевтический архив)
Aim. To evaluate the long-term safety and efficacy of goflkicept treatment in patients with idiopathic recurrent pericarditis (IRP).